Plant cell wall‐mediated immunity: cell wall changes trigger disease resistance responses - Bacete, Laura; Mélida, Hugo; Miedes, Eva; Molina, Antonio (The Plant journal : for cell and molecular biology, 2018)
Summary Plants have evolved a repertoire of monitoring systems to sense plant morphogenesis and to face environmental changes and threats caused by different attackers. These systems integrate different signals into overreaching triggering pathways which coordinate developmental and defence‐associated responses. The plant cell wall, a dynamic and complex structure surrounding every plant cell, has emerged recently as an essential component of plant monitoring systems, thus expanding its function as a passive defensive barrier. Plants have a dedicated mechanism for maintaining cell wall integrity (CWI) which comprises a diverse set of plasma membrane‐resident sensors and pattern recognition receptors (PRRs). The PRRs perceive plant‐derived ligands, such as peptides or wall glycans, known as damage‐associated molecular patterns (DAMPs). These DAMPs function as ‘danger’ alert signals activating DAMP‐triggered immunity (DTI), which shares signalling components and responses with the immune pathways triggered by non‐self microbe‐associated molecular patterns that mediate disease resistance. Alteration of CWI by impairment of the expression or activity of proteins involved in cell wall biosynthesis and/or remodelling, as occurs in some plant cell wall mutants, or by wall damage due to colonization by pathogens/pests, activates specific defensive and growth responses. Our current understanding of how these alterations of CWI are perceived by the wall monitoring systems is scarce and few plant sensors/PRRs and DAMPs have been characterized. The identification of these CWI sensors and PRR–DAMP pairs will help us to understand the immune functions of the wall monitoring system, and might allow the breeding of crop varieties and the design of agricultural strategies that would enhance crop disease resistance. Significance Statement The plant cell wall has emerged as an essential component of plant stress‐monitoring systems, thus expanding its function as a passive defensive barrier. Here we review current knowledge about the systems that monitor plant cell wall integrity and their functions in triggering specific disease resistance and growth responses.